Depressive symptoms, impaired glucose metabolism, high visceral fat, and high systolic blood pressure in a subgroup of women with recent gestational diabetes. (February 2018) - Ferrari, U.; Banning, F.; Freibothe, I.; Tröndle, K.; Sacco, V.; Wichmann, C.; Reif, S.; Moschko, S.; Potzel, A.; Gar, C.; Sommer, N.N.; Popp, D.; et al.
Abstract: Women with gestational diabetes (GDM) are a high risk group for early type 2 diabetes (T2D). Depression is a risk factor for T2D in the general population. We investigated in women after a recent pregnancy with GDM and without a clinical diagnosis of depression, whether mild to moderate depressive symptoms associate with pathologic glucose metabolism. In a cross-sectional analysis, we examined 173 women, 9 ± 3 months after delivery with several psychopathological assessments, 5-point oral glucose tolerance test with insulin, anthropometrics, and laboratory chemistry. In a subgroup of 101 women, abdominal visceral fat was quantified by magnetic resonance imaging (MRI). A total of 22 women (13%) showed mild to moderate depressive symptoms, and the proportion of women with pathologic glucose metabolism (impaired fasting glucose, impaired glucose tolerance, or T2D) was higher in this group than in the women without depressive symptoms (59.1% vs. 33.1%, p = 0.018). Women with depressive symptoms also had higher body mass index (BMI), systolic blood pressure, plasma leptin, plasma resistin, and abdominal visceral fat volume. Pathologic glucose metabolism (OR = 2.594, 95% CI: 1.021–6.592), systolic blood pressure (OR = 1.076, 95% CI: 1.027–1.128), and abdominal visceral fat volume (OR = 2.491, 95% CI: 1.142–5.433) remained, even after adjustment for BMI, associated with the presence of depressive symptoms. Taken together, we found depressive symptoms at a level not generally diagnosed in clinical practice in a subgroup of women with recent GDM. This subgroup also showed an unfavorable metabolic profile. Mild to moderate depressive symptoms may therefore help to identify this special subgroup.